Cerebral Blood Flow Disorder in Acute Subdural Hematoma and Acute Intraoperative Brain Bulge - Xian, Liang; Wang, Cheng; Wei, Liangfeng; Wang, Shousen (Frontiers in Neurology, 2022)
Context: Acute subdural hematoma (ASDH) has a high incidence and mortality. In clinical surgery for acute subdural hematoma, rapid swelling of brain tissue protruding into the bone window sometimes occurs during or after removal of the hematoma. This phenomenon progresses rapidly, and this condition can cause brain tissue ischemic necrosis or even death. The mechanism of this phenomenon, called acute intraoperative brain bulge, is still not clear. Objective: To investigate the changes in cerebral surface blood flow during acute subdural hematoma and acute intraoperative brain bulge in rats. Methods: Adult male SD rats were selected to establish an acute subdural hematoma model and induce acute intraoperative brain bulge. The changes in cerebral surface blood flow during acute subdural hematoma and acute intraoperative brain bulge were observed by a laser speckle imaging system, and intracranial pressure was monitored. Results: The intracranial pressure of acute subdural hematoma rats increased and remained high after the operation. Brain surface blood perfusion rate (BPR) decreased but recovered after 90 min. Intraoperative intracranial pressure in rats with acute intraoperative brain bulge was significantly increased, but it could be decreased by removing the inducement in time. Brain surface BPR decreased further in the acute intraoperative brain bulge group and recovered slightly after removing the inducement. Conclusion: Acute subdural hematoma may cause not only high cranial pressure but also cerebral blood circulation disorders, which may be a factor in secondary injury. Swelling of brain tissue can further lead to circulation problems. Cerebral circulation disorders may be causally associated with acute intraoperative brain bulge. Therefore, cerebral circulation problems in patients with craniocerebral injury should be considered before surgery, and cerebral circulation disorders should be prevented or treated in time during the operation and after.